Wild rodents and insectivores as carriers of pathogenic Leptospira and Toxoplasma gondii in The Netherlands - Krijger, Inge M. (Vet Med Sci, 2020)
Small mammals such as rodents can to carry zoonotic pathogens. Currently, there is impaired knowledge on zoonotic pathogens in rodents and insectivores in the Netherlands. This limits opportunities for preventive measures and complicates risk‐assessments for zoonotic transmission to humans. Leptospira spp. and Toxoplasma gondii are present on a list of prioritized emerging pathogens in the Netherlands and were therefore the focus of this study. Both pathogens have the ability to survive under moist environmental conditions. In total, a group of 379 small mammals (rodents & insectivores) were tested on pathogenic Leptospira spp., and 312 on T. gondii. Rodents and insectivores were trapped at various sites, but mostly on pig and dairy farms throughout the country. Over five percent of the animals (5.3%, n = 379) tested positive for Leptospira DNA, and five of the animals (1.6%, n = 312) tested were positive for T. gondii DNA. The animals positive for T.gondii were all brown rats and the ones for Leptospira spp. were various species. Our results show that insectivores and rodents might be used as an indicator for the environmental contamination and/or the contamination in wildlife for Leptospira spp.